Determinants of incident dementia in different old age groups: results of the prospective AgeCoDe/AgeQualiDe study. (23rd May 2020) - Luck, Tobias; Pabst, Alexander; Roehr, Susanne; Wiese, Birgitt; Eisele, Marion; Heser, Kathrin; Weeg, Dagmar; Fuchs, Angela; Brettschneider, Christian; Werle, Jochen; Mamone, Silke; Bussche, Hendrik van den; et al.
ABSTRACT: Objectives: To examine the impact of determinants of incident dementia in three different old age groups (75–79, 80–84, 85+years) in Germany. Design: Multicenter prospective AgeCoDe/AgeQualiDe cohort study with baseline and nine follow-up assessments at 1.5-year intervals. Setting: Primary care medical record registry sample. Participants: General practitioners' (GPs) patients aged 75+years at baseline. Measurements: Conduction of standardized interviews including neuropsychological assessment and collection of GP information at each assessment wave. We used age-stratified competing risk regression models (accounting for the competing event of mortality) to assess determinants of incident dementia and age-stratified ordinary least square regressions to quantify the impact of identified determinants on the age at dementia onset. Results: Among 3027 dementia-free GP patients, n = 704 (23.3%) developed dementia during the 13-year study period. Worse cognitive performance and subjective memory decline with related worries at baseline, and the APOE ε4 allele were associated independently with increased dementia risk in all three old age groups. Worse cognitive performance at baseline was also associated with younger age at dementia onset in all three age groups. Other well-known determinants were associated with dementia risk and age at dementia onset only in some or in none of the three old age groups. Conclusions: This study provides further evidence for the age-specific importance of determinants of incident dementia in old age. Such specifics have to be considered more strongly particularly with regard to potential approaches of early detection and prevention of dementia.